Association between depression and stroke risk in adults: a systematic review and meta-analysis - Ashraf, Farheen; Mustafa, Muhammad Saqlain; Shafique, Muhammad Ashir; Haseeb, Abdul; Mussarat, Abdullah; Noorani, Amber; Sohail Rangwala, Burhanuddin; Kashif Rasool, Fatimah; Siddiq, Mohammad Arham; Iqbal, Javed (Frontiers in Neurology, 2024)
Stroke is a significant global health concern, and numerous studies have established a link between depression and an increased risk of stroke. While many investigations explore this link, some overlook its long-term effects. Depression may elevate stroke risk through physiological pathways involving nervous system changes and inflammation. This systematic review and meta-analysis aim to assess the association between Depression and Stroke.We conducted a comprehensive search of electronic databases (PubMed, Embase, Scopus, PsycINFO) until April 9th, 2023, following PRISMA and MOOSE guidelines. We included all articles assessing the association between different stroke types and depression, excluding post-stroke depression. Two investigators independently extracted data and assessed quality using the Newcastle Ottawa Scale and Cochrane Risk of Bias tool, utilizing a random-effects model for data synthesis. The primary outcome was the association of depression with stroke, with a secondary focus on the association of antidepressants with strokeThe initial search yielded 10,091 articles, and 44 studies were included in the metaanalysis. The pooled analysis revealed a significant association between depression and stroke risk, with an overall hazard ratio of 1.41 (95% CI 1.32, 1.50; P < 0.00001), indicating a moderate positive effect size. Subgroup analyses showed consistent associations with ischemic stroke (